Strategi Penguatan Peran Instruktur Lokal dalam Pariwisata Spiritual di Ubud dengan Pendekatan Berbasis Kearifan Lokal Bali - I Gusti Bagus Angga Wiguna (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
Bali's local wisdom-based spiritual tourism in Ubud faces various challenges due to globalization and the growing influence of foreign healing methods. This study aims to analyze strategies for strengthening the role of local instructors in preserving and developing traditional Balinese spiritual practices. Using SWOT analysis, this research evaluates internal and external factors affecting the sustainability of local instructors' roles. Data were collected through in-depth interviews with influential cultural figures and local spiritual practitioners. The findings indicate that strengthening the role of local instructors can be achieved through human resource capacity building, digital technology utilization for promotion, and regulations protecting traditional spiritual practices. Additionally, collaboration with various stakeholders, including the government and the tourism sector, is essential to ensure the sustainability of culture-based spiritual tourism in Bali.